Design and studies of monopole antenna integrated with metamaterial-based CSRR and rectangular spiral shaped for super wide band application - Nurhayati, Nurhayati; Al Gburi, Ahmed Jamal Abdullah; Zulkifli, Fitri Yuli; Rombe, Ali Hanafiah; Firdaus, Rohim Aminullah; Edy Purnomo, Muhammad Fauzan; Thuy Le, Minh (Elsevier B.V., 2025)
Telecommunications technology in the Super Wide Band (SWB) frequency is crucial for numerous applications including short- and long-distance communication. This study examines the effect of wavy structure at the top edge of the patch, the variation of ground height, the shape and the location of Complimentary Split Ring Resonator (CSRR), and square spiral structure to a semi-elliptical monopole antenna performance. Parametric studies were used to evaluate the antenna's reflection coefficient, directivity, band notched frequency, and axial ratio. Simulation results show that the antenna has a reflection coefficient of less than -15 dB at most frequencies from 0.38 to more than 20 GHz. The Wavy structure type A monopole antenna has a directivity of 6.12 dBi at 2 GHz, whereas type B has 3,985 dBi. However the highest gain for Antenna Type-C is 7.45dBi. Especially at low frequencies, ground height affects antenna return loss. Several notched band frequencies and circular polarization can be generated on the antenna by providing a rectangular spiral structure on the groundplane or a CSRR structure at the base of the patch. The minimum axial ratio (AR) is 1.11 dB at frequencies from 5.965 GHz to 6.585 GHz and 0.56 dB at 2 GHz when the spiral structure height is varied. There is agreement on the antenna's performance between the experimental and simulation results. The antenna has been utilized in through-wall radar, therefore it can be used to improve Super Wide Band radar and communications systems.